Pengembangan Media Pembelajaran IPAS Berbasis Wordwall untuk Meningkatkan Hasil Belajar Peserta Didik - Shelvia Amanda; Syahira Nabila Zulkim; Adrias Adrias; Nur Azmi Alwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to see the development of student learning outcomes using Wordwall-based science and technology learning media in grade IV SDN 01 Muara Panas, Solok Regency. This type of research uses a qualitative descriptive research method. Qualitative descriptive research is a series of activities carried out to obtain data that is as it is in accordance with the data in the field. The stages of data collection in this study are observation and interviews. The data collection analysis technique is to provide media, present data, and receive conclusions. The results of the study used Wordwall teaching media in improving the learning outcomes of grade IV students of SDN 01 Muara Panas, Solok Regency. Researchers use Wordwall media because this teaching media can be accessed easily and free of charge by teachers. Wordwall media also presents a variety of diverse alternative media such as Open the Box, True or False, Random Wheel, Missing Word, Find the Match, and many other types. With the presentation of various alternative media, educators can be creative in presenting fun teaching media for students. Fun teaching media will make students more active in participating in learning.